Intelligibility: different persceptives of its concep and assessment. A systematic review - Malatesta Haug, Gisella; Pérez Herrera, Denisse (Revista de Investigación en Logopedia, 2021)
Adequate intelligibility is an indicator of successful communication. Their interference, due to any pathology, must be addressed in the primary goals of therapy. However, the methods for its evaluation are poorly understood. Objective: to develop a systematic review that describes the methods used to measure intelligibility and discuss the conceptualization of this construct. Methods: a search was carried out in the PubMed, ScieLo and Science Direct databases to identify articles published between 1990 and 2018. Analysis and discussions: 50 investigations were selected in English, Spanish and Portuguese, showing preferences for objective evaluation measures, over subjective measures of scale. Intelligibility is better defined as a construct dependent on the acoustic signal, as opposed to the concept of comprehensibility. This review provides updated and organized information for clinical and scientific procedures for measuring intelligibility.
Keywords: Evaluation; Intelligibility; Measurement